CHARACTERIZING OF TUNA FISHERIES ASSOCIATED WITH FADS IN INDONESIA FMA 713-717 - Widodo, Agustinus Anung; Wudianto, Wudianto; Proctor, Craig; Satria, Fayakun; Hargiyatno, Ignatius T; Sadiyah, Lilis (Jakarta Technical University of Fisheries, 2022)
To support improving fisheries management on tuna fisheries in Indonesia FMA (I-FMA) 713-717, an Indonesia - Australia research collaboration conducted a study during November 2013 – December 2015 at two key tuna fishing bases including Kendari (Southeast Sulawesi) and Sorong (West Papua). This study involved an enumeration program with skipper interviews, direct observations and biological sampling. The study showed that all fish aggregating devices (FADs) in Indonesian waters are anchored fish aggregating devices (aFADs). Three main fisheries associated with aFADs include purse-seine (PS), pole and line (PL) and hand-line (HL). The PL fishery based in Sorong had the highest FAD-success rate-FSR (84.9 %) compared to other fisheries including PL and HL based in Kendari. The average catch rates of PL and PS boats based in Sorong 2013-2015 were 10,352 and 33,854 kg/trip/boat respectively. The average catch rates of PL and HL boats based in Kendari were 2,819 and 1,135 kg/trip/boat respectively. Apart from the catch of HL based in Kendari, the largest proportion of the catch was juvenile yellowfin tuna (j-YFT) and juvenile bigeye tuna (j-BET). The proportion of sharks and billfish as by-catch species, in the landings of HL and PL boats based in Kendari and Sorong was extremely low.